2005
DOI: 10.4028/www.scientific.net/amr.6-8.163
|View full text |Cite
|
Sign up to set email alerts
|

Flux-Less Joining Technique of Aluminium with Zinc-Coated Steel Sheets by a Dual-Spot-Laser Beam

Abstract: Joining of iron with aluminium in the liquid phase is complicated due to the formation of brittle intermetallics within Fe-Al melts. In this work we present the technology of a laser weldingbrazing (LWB) process to join zinc-coated steel and aluminium sheets in an overlap geometry. The process is divided into welding of the aluminium sheet and brazing of filler material and molten aluminium sheet onto the zinc-covered steel sheet to avoid the liquid stage of iron. It is possible to join those materials with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the joining of dissimilar alloys, laser welding method provides some advantages such as high energy density, rapid heating/cooling velocity and accessibility to the heating zone [20,21]. Specially, the laser welding-brazing method to attach metallurgical non-fitting partners to each other can suppress effectively the growth of brittle intermetallic compounds [22][23][24][25]. Hence, tensile strength of the joint by laser welding-brazing was enhanced significantly.…”
Section: Introductionmentioning
confidence: 96%
“…In the joining of dissimilar alloys, laser welding method provides some advantages such as high energy density, rapid heating/cooling velocity and accessibility to the heating zone [20,21]. Specially, the laser welding-brazing method to attach metallurgical non-fitting partners to each other can suppress effectively the growth of brittle intermetallic compounds [22][23][24][25]. Hence, tensile strength of the joint by laser welding-brazing was enhanced significantly.…”
Section: Introductionmentioning
confidence: 96%
“…The tensile property was supposed by expressing as the maximal Most recently, dual-beam laser welding has been introduced for dissimilar welding of steel/Al joints. Laukant et al [34] reported that the melt flow could be controlled more effectively and the wetting behavior could be improved by preheating the zinc-covered steel sheet surface with a second laser beam when joined zinc-coated steel and Al sheets in overlap geometry. Shi et al [35] demonstrated that the application of a dual-beam laser keyhole welding could generate an acceptable steel/Al joint and effectively reduced the presence of the welding defects.…”
Section: Introductionmentioning
confidence: 99%
“…Very good brazing beads are obtained both in lap joints ISSN and frame joints. Figure 3 shows the appearance of dual-beam YAG laser brazed (lap) joint of A6061 alloy and GA (DX56D þ Z140 MB) made using Al-Mg -Mn filler 5 . With GA, it has been reported that good brazing can be achieved even without the use of flux, and for curved.…”
Section: The Principles and Characteristics Of Laser Weldingmentioning
confidence: 99%